OPTIMIZING PROJECT-BASED LEARNING TO IMPROVE SOCIAL AWARENESS AMONG SENIOR HIGH SCHOOL STUDENTS - Ernawati (CV. Fahr Publishing, 2025)
This study aims to optimize Project-Based Learning (PBL) as a pedagogical approach to enhance social awareness among senior high school students. The research is grounded in the increasing need for education systems to promote not only academic achievement but also the development of civic responsibility, empathy, and ethical sensitivity. Employing a library research method, this study systematically analyzed recent literature from the past five years, focusing on PBL practices in diverse educational settings. The data were collected through thematic content analysis of scholarly articles, which were reviewed and categorized to identify key components and outcomes of PBL related to social awareness. Findings reveal that while PBL has consistently improved student skills in empathy, collaboration, and responsibility, outcomes such as civic knowledge and ethical sensitivity remain inconsistently addressed across implementations. A key novelty of this research lies in its development of a conceptual framework that integrates community-based tasks, structured student reflection, teacher facilitation, and school culture as interrelated variables that influence social-awareness development. Furthermore, the study contributes contextually by examining these elements within the Indonesian high school context, providing geographical and cultural diversity to existing PBL literature. The conclusion highlights that PBL, when purposefully designed and supported institutionally, can serve as an effective tool for fostering socially responsible learners. This research provides both theoretical and practical insights for educators, policymakers, and curriculum developers interested in leveraging PBL to meet global education goals related to citizenship and social competence.